MENINGKATKAN KEMAMPUAN KOMUNIKASI MELALUI METODE KOMUNIKASI TOTAL BAGI ANAK TUNARUNGU KELAS II DI SLB KARTINI BATAM - Sulastri - Sulastri (Jurnal Penelitian Pendidikan Khusus, 2013)
Improving Communication Skills Through Methods Total In Children Deaf Communication Medium Class II Kartini SLB Batam. Thesis Department of Exceptional Education FIP Padang State University. This study motivated the children - children with hearing impairment in Extraordinary School Kartini was difficulty in communicating with others. In general, this is because their vocabulary is very little, not good at reading and understanding the meaning of each word delivered in communications, so they look very passive in communicating with others and in the learning activities. The purpose of this study to gain a clear picture of increased ability to communicate with deaf children were in total communication methods. This study is an action research (classroom action research) in which researchers directly involved in the implementation of the action. The study design developed include: 1) planning, 2) action, 3) observations, and 4) Reflection. Subjects were deaf students were class II of six people, three women and three men - men. Data were collected by using the technique of observation, discussion and documentation. The results achieved by the six students during the training cycle is still quite have not succeeded completely, because there are two students who are having difficulty in understanding the message conveyed by his interlocutor. In the second cycle, achieved better results. This occurred after the individual service, motivation and learning media is more diverse and interesting, looks sixth learners are able to understand the message and interact in the activities of communication is much better than before. Results showed that deaf children's communication skills are on the rise with total communication methods, individualized service delivery, motivation and use of learning media is more interesting.